Erlotinib regulates short-term memory, tau/Aβ pathology, and astrogliosis in mouse models of AD - Lee, Hyun-ju; Hwang, Jeong-Woo; Kim, Jieun; Jo, A-Ran; Park, Jin-Hee; Jeong, Yoo Joo; Jang, Ji-Yeong; Kim, Su-Jeong; Song, Jeong-Heon; Hoe, Hyang-Sook (Frontiers in Immunology, 2024)
Erlotinib is an epidermal growth factor receptor (EGFR) inhibitor that is approved by the FDA to treat non-small cell lung cancer (NSCLC). Several membrane receptors, including EGFR, interact with amyloid  (A), raising the possibility that erlotinib could have therapeutic effects on Alzheimer's disease (AD). However, the effects of erlotinib on Aβ/tau-related pathology and cognitive function in mouse models of AD and its mechanisms of action have not been examined in detail. In this study, we investigated the effects of erlotinib on cognitive function and found that erlotinib significantly enhanced short-term spatial memory and dendritic spine formation in 6-month-old P301S tau transgenic (PS19) mice. Importantly, erlotinib administration reduced tau phosphorylation at Ser202/Thr205 (AT8) and Thr231 (AT180) and further aggregation of tau into paired helical fragments (PHFs) and neurofibrillary tangles (NFTs) in 3-month-old and/or 6-month-old PS19 mice by suppressing the expression of the tau kinase DYRK1A. Moreover, erlotinib treatment decreased astrogliosis in 6-month-old PS19 mice and reduced proinflammatory responses in primary astrocytes (PACs) from PS19 mice. In 3- to 3.5-month-old 5xFAD mice, erlotinib treatment improved short-term spatial memory and hippocampal dendritic spine number and diminished Aβ plaque deposition and tau hyperphosphorylation. Furthermore, erlotinib-treated 5xFAD mice exhibited significant downregulation of astrocyte activation, and treating PACs from 5xFAD mice with erlotinib markedly reduced cxcl10 (reactive astrocyte marker) and gbp2 (A1 astrocyte marker) mRNA levels and proinflammatory cytokine mRNA and protein levels. Taken together, our results suggest that erlotinib regulates tau/Aβ-induced AD pathology, cognitive function, and Aβ/tau-evoked astrogliosis and therefore could be a potent therapeutic drug for ameliorating AD symptoms.